Intraocular Lens - Wang, Xiaogang; Ferreri, Felicia M. (IntechOpen, 2020)
The first clinical application of intraocular lens (IOL) goes back to 1949 when Dr. Harold Ridley successfully implanted a PMMA IOL into an eye on 29 November 1949. This innovation is a big step forward for cataract surgery. With development of the IOL material and biocompatibility, more and more IOL types have been used in clinical ophthalmology. This book is the fruit of worldwide cooperation between clinical teams. In this book we discuss the IOL materials and design, aberration and astigmatism correction with IOL, entopic phenomenon of IOL, myopia and phakic IOL, and secondary IOL techniques. We believe that this content provides the readers with a comprehensive knowledge of the latest developments of IOL.